Bluetongue Dynamics in French Wildlife: Exploring the Driving Forces. Issue 6 (18th February 2013) - Rossi, S.; Pioz, M.; Beard, E.; Durand, B.; Gibert, P.; Gauthier, D.; Klein, F.; Maillard, D.; Saint‐Andrieux, C.; Saubusse, T.; Hars, J.
Summary Bluetongue (BT) was monitored in wildlife in France during two consecutive years corresponding to contrasting incidence rates in livestock: in 2008 at the peak of domestic outbreaks and in 2009 when very few outbreaks were observed. The disease status of 2 798 ruminants comprising 837 red deer (Cervus elaphus) was explored using ELISA test on serum and real‐time RT‐PCR test on blood or spleen. A large proportion of red deer were seropositive and positive to RT‐PCR in 2008, but also in 2009 (seroprevalence: 47.1% and 24.3%), suggesting that red deer could maintain infection when domestic incidence was negligible. By contrast, low seroprevalence (<3%) and few RT‐PCR positive results were observed in other wild ruminant species, which rather appeared thus as dead‐end hosts. The risk factors of bluetongue circulation during the periods of high (2008) and low (2009) domestic incidence were explored in red deer using logistic mixed models. In this species, prevalence has been mainly influenced by the initial peak of BT in livestock, but also by environmental factor such as elevation and edge density between forest and pastures. Surprisingly, cattle density has a negative influence on prevalence in red deer, possibly due to the protective effect of cattle regarding midges' bites and/or to still unexplained factors dealing with the host/midge interface. To our knowledge, this study is the first attempt at measuring the effect of landscape and wildlife/domestic interface on BT prevalence in wildlife in Europe.